Decision making in mental health team meetings - Narayanasamy, Melanie Jay (RCN Publishing, 2016)
Background: Single point of access meetings represent a critical juncture in the lives of mental health clients. The decision-making process undertaken by mental health professionals during this time is therefore crucial.